The Promise and Failure of the American Dream in Scott Fitzgerald’s Fiction - Ghasemi, Parvin; Tiur, Mitra (k@ta: A Biannual Publication on the Study of Language and Literature, 2010)
The Great Gatsby is Fitzgerald’s best fictional account of the promise and failure of the American dream because here the congruity of story and style and attitude is most meaningful to the depiction of this theme. Fitzgerald created Gatsby and his myth to be an emblem of the irony and the corruption of the American dream. Fitzgerald was the embodiment of the fluid polarities of American experience: success and failure, illusion and disillusion, dream and nightmare. The exhaustion of the frontier and the rebound of the post war expatriate movement marked for Fitzgerald as the end of a long period in human history, the history of the Post-Renaissance man in America, that he made the substance of his works. Fitzgerald’s ideology, a serious criticism on the American Dream, reveals the real nature of American life so that he could find a way to the truth of the American identity.